Understanding about gambling that related to the contest among UiTM Cawangan Selangor, Kampus Puncak Alam students / Ameen Soleh Mohamad Ramli - Mohamad Ramli, Ameen Soleh (2019)
This study examine the understanding about gambling that related to the contest among the students of UiTM Cawangan Selangor, Kampus Puncak Alam. The understanding needs to be understood because of the law of banning it and the ignorance of students. A survey data by the respondents of students using Statistical Package for Social Sciences (SPSS). Results reveal a weak significant about understanding against faculty and semester. Moreover, the purpose of this study is to look at the extent to which students understand gambling. To conclude, the study reveals the extent to which students' understanding of gambling concept.